2018
DOI: 10.1029/2018gl081183
|View full text |Cite
|
Sign up to set email alerts
|

What Caused the Accelerated Sea Level Changes Along the U.S. East Coast During 2010–2015?

Abstract: Accelerated sea level rise was observed along the U.S. eastern seaboard south of Cape Hatteras during 2010–2015 with rates 5 times larger than the global average for the same time period. Simultaneously, sea levels decreased rapidly north of Cape Hatteras. In this study, we show that accelerated sea level rise recorded between Key West and Cape Hatteras was predominantly caused by a ~1 °C (0.2 °C/year) warming of the Florida Current during 2010–2015 that was linked to large‐scale changes in the Atlantic Warm P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
87
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 36 publications
9
87
1
Order By: Relevance
“…During those 25 years, warming of the ocean can be seen especially in recent years as steric SSH rises. These results are consistent with the findings of Domingues et al (2018) who showed that between 2015 to 2017 temperature in the Florida Strait shifted from about −1°C cold anomaly to about +1°C warm anomaly. The difference in SSH (Figure 3c) shows the recent shift from a period of (relatively) higher SSH in the north (2009)(2010)(2011)(2012)(2013) to a period of (relatively) higher SSH in the south (2014-2017).…”
Section: 1029/2019ef001174supporting
confidence: 93%
See 4 more Smart Citations
“…During those 25 years, warming of the ocean can be seen especially in recent years as steric SSH rises. These results are consistent with the findings of Domingues et al (2018) who showed that between 2015 to 2017 temperature in the Florida Strait shifted from about −1°C cold anomaly to about +1°C warm anomaly. The difference in SSH (Figure 3c) shows the recent shift from a period of (relatively) higher SSH in the north (2009)(2010)(2011)(2012)(2013) to a period of (relatively) higher SSH in the south (2014-2017).…”
Section: 1029/2019ef001174supporting
confidence: 93%
“…These results are consistent with the findings of Domingues et al (2018) who showed that between 2015 to 2017 temperature in the Florida Strait shifted from about −1°C cold anomaly to about +1°C warm anomaly. These oscillations are different in phase and amplitude for the northern and southern regions, thus pointing to different dynamic regional forcing as suggested before (Domingues et al, 2018;Valle-Levinson et al, 2017;Woodworth et al, 2016). Oscillations with periods of 2-5 years clearly impact the trends as seen from the low-pass filtered records (heavy black lines in Figure 3; these lines were obtained from the low-frequency EMD modes, as discussed later).…”
Section: 1029/2019ef001174supporting
confidence: 93%
See 3 more Smart Citations